The dynamic clustering of insulin receptor underlies its signaling and is disrupted in insulin resistance - Dall’Agnese, Alessandra; Platt, Jesse M.; Zheng, Ming M.; Friesen, Max; Dall’Agnese, Giuseppe; Blaise, Alyssa M.; Spinelli, Jessica B.; Henninger, Jonathan E.; Tevonian, Erin N.; Hannett, Nancy M.; Lazaris, Charalampos; Drescher, Hannah K.; et al. (Nature communications, 2022)
Insulin receptor (IR) signaling is central to normal metabolic control and is dysregulated in metabolic diseases such as type 2 diabetes. We report here that IR is incorporated into dynamic clusters at the plasma membrane, in the cytoplasm and in the nucleus of human hepatocytes and adipocytes. Insulin stimulation promotes further incorporation of IR into these dynamic clusters in insulin-sensitive cells but not in insulin-resistant cells, where both IR accumulation and dynamic behavior are reduced. Treatment of insulin-resistant cells with metformin, a first-line drug used to treat type 2 diabetes, can rescue IR accumulation and the dynamic behavior of these clusters. This rescue is associated with metformin’s role in reducing reactive oxygen species that interfere with normal dynamics. These results indicate that changes in the physico-mechanical features of IR clusters contribute to insulin resistance and have implications for improved therapeutic approaches. The authors find that the insulin receptor forms dynamic clusters during insulin signaling and that these clusters become dysfunctional in insulin resistance. This dysfunction is partially rescued by metformin, a drug used to treat type 2 diabetes.